Dual-Side Phase-Shift Control for Strongly Coupled Series–Series Compensated Electric Vehicle Wireless Charging Systems - Yiming Zhang; Zhiwei Shen; Yuanchao Wu; Hui Wang; Wenbin Pan (World Electric Vehicle Journal, 2021)
Wireless power transfer (WPT) for electric vehicles is an emerging technology and a future trend. To increase power density, the coupling coefficient of coils can be designed to be large, forming a strongly coupled WPT system, different from the conventional loosely coupled WPT system. In this way, the power density and efficiency of the WPT system can be improved. This paper investigates the dual-side phase-shift control of the strongly coupled series–series compensated WPT systems. The mathematical models based on the conventional first harmonic approximation and differential equations for the dual-side phase-shift control are built and compared. The dual-side phase-shift angle and its impact on the power transfer direction and soft switching are investigated. It is found that synchronous rectification at strong couplings can lead to hard switching because the dual-side phase shift in this case is over 90°. In comparison, a relatively high efficiency and soft switching can be realized when the dual-side phase shift is below 90°. The experimental results have validated the analysis.